ADMINISTRATIVE PROCESS IN BRAZILIAN MUNICIPALITIES: CRITICAL ANALYSIS IN SEARCH OF EFFECTIVE GUARDIANSHIP OF RIGHTS AND ACCESS TO FAIR LEGAL ORDER - Mota Gutiérrez, Daniel; Dantas Alves, Mestr. Fridtjof Chrysostomus (Revista Inclusiones, 2021)
The protection of rights is not a unique and exclusive function of the Judiciary Power, with the administrative process being an effective means of protecting them, ensuring not only the resolution of conflicts, but also the excessive proliferation of legal disputes involving the public administration. In this reality, the use of the administrative process in medium and small-sized Brazilian municipalities is critically analyzed, observing how it is necessary to improve it, also demonstrating which impacts are caused by its poor use, in order to present how the process administrative can be improved, considering the available resources and the current legislation, pointing out which benefits are obtained with its proper adequacy.